SINGLE-CRYSTAL X-RAY DIFFRACTION STUDY OF CATION DISTRIBUTION IN MGAL2O4-MGFE2O4 SPINEL SOLID SOLUTION - Nakatsuka A.; Ueno H.; Nakayama N.; Mizota T.; Maekawa H. (My University, 2004)
Synthesis experiments in the system MgAl2O4–MgFe2O4 [MgAl2−x Fex O4 (0 ≤ x ≤ 2)] were carried out using a PbF2 flux. The crystalline products synthesized in the compositional range of 0.6 <x ≤ 1.2 consisted of two spinel phases, whereas those synthesized in the compositional ranges of 0.0 ≤ x ≤ 0.6 and 1.2 < x ≤ 2.0 crystallized as single spinel phases. Structure refinements of the spinel single crystals, which grew in the ranges of 0.0 ≤ x ≤ 0.6 and 1.2 < x ≤ 2.0, show that the degree of randomness of cation distribution between A and B sites increases as x approaches the two-phase region. This means that the degree of the size mismatch among Mg2+, Fe3+ and Al3+occupying each equivalent mixing site increases as x approaches the two-phase region. Consequently, if the coexistence of two spinels observed in the intermediate compositions reveals the existence of a miscibility gap at low temperatures, this increase in the degree of the size mismatch among the three cations is suggested as a factor of energetic destabilization to form the miscibility gap.
Keywords: Spinel; Solid solution; Cation distribution; Miscibility gap; Single-crystal X-ray diffraction